2003
DOI: 10.1002/syn.10249
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of three vesicular glutamate transporter mRNAs and proteins in rat spinal cord and dorsal root ganglia

Abstract: Glutamate is transported into synaptic vesicles by vesicular glutamate transporter (VGLUT) proteins. Three different VGLUTs, VGLUT1, VGLUT2, and VGLUT3, have recently been characterized, and they are considered to represent the most specific marker so far for neurons using glutamate as transmitter. We analyzed the cellular localization of VGLUT1-3 in the rat spinal cord and dorsal root ganglia (DRGs) in control rats and after dorsal rhizotomy. Using in situ hybridization, VGLUT1 mRNA containing neurons were sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

55
252
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(315 citation statements)
references
References 58 publications
(85 reference statements)
55
252
7
Order By: Relevance
“…This antibody labels a single band of appropriate molecular weight (≈62 kDa) in Western blots of synaptic vesicle fractions of rat brains (Synaptic Systems, Goettingen, Germany). In our spinal cord sections the laminar distribution of immunolabeled puncta (high densities in LIII-LV, LVII, and LIX; weaker densities in LI and LII and LVIII) is identical to that previously published by us Mentis et al, 2006) and other authors using this or similar antibodies raised in different species (Todd et al, 2003;Oliveira et al, 2003).…”
Section: Marker Antibodiessupporting
confidence: 88%
See 2 more Smart Citations
“…This antibody labels a single band of appropriate molecular weight (≈62 kDa) in Western blots of synaptic vesicle fractions of rat brains (Synaptic Systems, Goettingen, Germany). In our spinal cord sections the laminar distribution of immunolabeled puncta (high densities in LIII-LV, LVII, and LIX; weaker densities in LI and LII and LVIII) is identical to that previously published by us Mentis et al, 2006) and other authors using this or similar antibodies raised in different species (Todd et al, 2003;Oliveira et al, 2003).…”
Section: Marker Antibodiessupporting
confidence: 88%
“…This antibody labels a single band of appropriate molecular weight (≈62 kDa) in Western blots of synaptic vesicle fractions of rat brains (Synaptic Systems, Goettingen, Germany). In our spinal cord sections the laminar distribution of immunolabeled puncta (high densities in LIII-LV, LVII, and LIX; weaker densities in LI and LII and LVIII) is identical to that previously published by us Mentis et al, 2006) and other authors using this or similar antibodies raised in different species (Todd et al, 2003;Oliveira et al, 2003).Vesicular acetylcholine transporter (VAChT) antibodies: We used two polyclonal antibodies raised in guinea pig and goat, respectively, each against a similar, but not identical, sequence in the C-terminus (see Table 1). By Western blot the guinea pig antibody reacted with a single band in rat brain homogenates that corresponded to the size predicted for VAChT (Chemicon, Temecula, CA).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The present study examined the relationship of VGlut2, VGlut3 transporters and NKI receptors with fos-I nuclei as both glutamate and NKI receptors have been shown to regulate pelvic reflexes [64,69]. Glutamate is the major excitatory neurotransmitter and recent studies have documented the distribution of glutamate transporters in the lumbosacral cord [2,34,38,51,57,63]. Studies have suggested that VGlut1 and VGlut2 expression is restricted to glutaminergic neurons; however, VGlut3 expression is found not only in glutaminergic neurons but also neurons that contain acetylcholine and serotonin [28].…”
Section: Discussionmentioning
confidence: 96%
“…VGlut2 also innervates the parasympathetic preganglionic neurons of the lumbosacral spinal cord [38]. In contrast, the distribution of VGlut3 has been less well studied, and existing data suggests that VGlut3 exhibits a more restricted expression pattern compared to VGlut1 and VGlut2 [50,51]. VGlut3 has been shown in some cholinergic and serotonergic neurons in the brain and pelvic function is modulated by serotonergic and cholinergic supraspinal and spinal pathways [27,28,43].…”
Section: Introductionmentioning
confidence: 99%